THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON THE PURCHASE DECISION OF YAMAHA MOTORCYCLES AT PT. JAYA MANDIRI GEMA SEJATI CIBINONG BRANCH - BOGOR - Baliyah Munadjat; Putri Nilam Kencana; Ading Sunarto (International Journal of Social Science, 2022)
This study aims to determine how big the influence of product quality and price on purchasing decisions for Yamaha motorcycles at PT. Jaya mandiri Gema sejati Cibinong Branch – Bogor. This research method uses the associative method, with 98 respondents as respondents. Data collection techniques to determine the effect of product quality and price on purchasing decisions using the services of Mr. Head Barbershop in September, October and November 2018. Instrument testing uses validity and reliability tests, data analysis with classical assumption test, multiple linear regression test, coefficient of determination, and hypothesis testing (t test and f test). The results of the study show that: Ho1 Partially, the product quality and price variables on purchasing decisions are equal to (9,767 > 1,660), so Ho1 is rejected and Ha1 is accepted. Ho2 value of t count > t table (2.592 > 1985), so it can be concluded that H1 is accepted which means it has a significant (positive) effect on the level of purchasing decisions on Yamaha motorcycles at PT. JayamandiriGemasejati. Ho3 partially, the price variable on purchasing decisions is (193.60 > 2.70), so Ho3 is rejected and Ha is accepted and the value of t count > t table (.000b < 0.1), which means the independent variable (X1 and X2) so that it can be concluded that jointly it has a significant effect on the variable (Y). The value of the coefficient of determination obtained R square value of 0.800 or 80%, which means that the influence of product quality and price on purchasing decisions is 80% and the remaining 20% ​​is influenced by other factors outside of this study.